Evaluation of contamination risks in Metallic Trace Elements (MTE) in the sediments of Ouémé delta in Benin - ADECHINA, Rodrigue; KELOME AHOUANGNIVO, MARIE THÉRÈSE M.; KAKI, CHRISTOPHE; HOUNKPE, Jéchonias (My University, 2019)
The Metallic Trace Elements (MTE) pollution of aquatic ecosystems and their intrusion and inclusion into the food chain exposes public health to enormous risks. This study assesses the risks associated with the pollution of surface sediments from Ouémé delta with Pb. Cu and Cd. In these sediments stratifications, the physicochemical characteristics of the sediments were evaluated. Total metal contents are determined by the inductively coupled plasma mass spectrometer. Risk indices are evaluated, followed by statistical processing in software R 3.3.2. On average, the pH is 5.50; the CEC is 84.24 meq / 100g and the organic carbon (OC) is 0.84 % of mass sediment. Means of Al2O3, Fe2O3 and CaO are respectively 8.14 %; 3.9 % and 6.08 %. The means of copper, lead and cadmium are respectively 32.92 ppm; 23.63 ppm and 1.43 ppm. Overall the degrees of risk related to contamination and ecological risks are low to high. Sites with a high degree of contamination and high ecological risk reflect the importance of the contribution of solid waste from Dantokpa market and the domestic discharges into the metal pollution of Ouémé delta.
Keywords: Ouémé delta; Sediments; Metallic Trace Elements; Risk of contamination; Ecological risk